Operationalizing niche construction theory with stone tools. Issue 1 (21st January 2021) - Iovita, Radu; Braun, David R.; Douglass, Matthew J.; Holdaway, Simon J.; Lin, Sam C.; Olszewski, Deborah I.; Rezek, Zeljko
Abstract: One of the greatest difficulties with evolutionary approaches in the study of stone tools (lithics) has been finding a mechanism for tying culture and biology in a way that preserves human agency and operates at scales that are visible in the archaeological record. The concept of niche construction, whereby organisms actively construct their environments and change the conditions for selection, could provide a solution to this problem. In this review, we evaluate the utility of niche construction theory (NCT) for stone tool archaeology. We apply NCT to lithics both as part of the "extended phenotype" and as residuals or precipitates of other niche‐constructing activities, suggesting ways in which archaeologists can employ niche construction feedbacks to generate testable hypotheses about stone tool use. Finally, we conclude that, as far as its applicability to lithic archaeology, NCT compares favorably to other prominent evolutionary approaches, such as human behavioral ecology and dual‐inheritance theory.